A dialogic reading of Luke 8:1–3 - Hombana, Mphumezi; Saleh Jnr, Jurgoi (Hervormde teologiese studies, 2025)
In this article, the topic of patronage in ancient Roman Palestine is discussed from the viewpoint of God as a benefactor who bestows grace on the early Christians. The article suggests that Luke 8:1–3 describes the women as ἀσθενής (those without adequate strength), portraying them as clients who received a gift and reciprocated in loyalty and gratitude. The perspective sheds light on the women within the ancient patronage culture, where there is no such thing as a gift without reciprocation. It argues that patronage, as an integral part of human existence, was ominously linked for the ancients (as with many ‘societies’ today). It is, however, argued here that the theme, as defined by its content and meaning in multiple contexts, forms an interpretive paradigm for understanding Luke 8:1–3. The article concludes that the appropriate human response to a gift from God is gratitude. The study concludes with some reflections on the theme in African society, particularly South African and Nigerian contexts, which have largely been characterised by these ancient attributes.ContributionThis article contributes to discussions on ancient patronage by framing God as a benefactor and the women in Luke 8:1–3 as clients who reciprocate divine gifts with loyalty and gratitude. It highlights the pervasive nature of patronage in antiquity and its parallels in contemporary societies, particularly in South Africa and Nigeria. By interpreting the women as ἀσθενής, it underscores their social vulnerability and dependence on divine favour. The study offers patronage as an interpretive lens for understanding Luke 8:1–3, emphasising gratitude as the proper response to divine benefaction. Ultimately, it bridges biblical patronage with African socio-cultural contexts.